2011
DOI: 10.1007/s00264-010-1189-z
|View full text |Cite
|
Sign up to set email alerts
|

Reamer-irrigator-aspirator indications and clinical results: a systematic review

Abstract: Background The 'reamer-irrigator-aspirator' (RIA) is an innovation developed to reduce fat embolism (FE) and thermal necrosis (TN) that can occur during reaming/ nailing of long-bone fractures. Since its inception its indications have expanded to include the treatment of long-bone osteomyelitis and as a harvester of bone graft/ mesenchymal stem cells (MSCs). Methods This study involved a systematic review, via Pubmed® and Google Scholar®, of English language sources (nine non-clinical studies, seven clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 47 publications
(103 reference statements)
1
85
0
7
Order By: Relevance
“…The innovation driven by the RIA systems was so significant, that the Journal "Injury" has dedicated a complete issue to the data available on RIA and its applications recently (71). A systematic review on the Reamer-irrigator-aspirator indications and clinical results has recently been published by Cox et al (72). The Masquelet technique as well as the RIA-system is nowadays frequently used in clinical practice, independently.…”
Section: Bone Grafting and Bone Substitutes In The Last 4 000 Yearsmentioning
confidence: 99%
“…The innovation driven by the RIA systems was so significant, that the Journal "Injury" has dedicated a complete issue to the data available on RIA and its applications recently (71). A systematic review on the Reamer-irrigator-aspirator indications and clinical results has recently been published by Cox et al (72). The Masquelet technique as well as the RIA-system is nowadays frequently used in clinical practice, independently.…”
Section: Bone Grafting and Bone Substitutes In The Last 4 000 Yearsmentioning
confidence: 99%
“…The RIA system can be used in an antegrade or retrograde fashion, and the technique is described in multiple papers [15][16][17][18][19] . After the bone graft harvest site is closed and sterile dressings have been applied, the graft is placed in a sterile cup on the back table.…”
Section: Description Of Procedurementioning
confidence: 99%
“…Although it is advantageous compared to standard iliac crest graft harvesting in terms of graft volume, donor side morbidity and possibly quality of graft [1,3,7], it is not without complications. Previous studies have highlighted the possibility of fractures and cortical breaching [1,2,[4][5][6]. Although the possibility of significant blood loss has also been mentioned in the majority …”
Section: Discussionmentioning
confidence: 99%
“…Its indications have expanded since then, and it is now used for intramedullary debridement for the treatment of osteomyelitis and for bone graft harvesting [1,2]. of these studies [2,[4][5][6]8], there are not many reported cases with massive blood loss. Quintero et al6reported on 20 cases; one of them developed intraoperative hypovolemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation